Design of an electrogoniometer based on accelerometers for the evaluation of sports gesture in weight lifting (2014)
This article describes the design and implementation of an electrogoniometer to measure joint angles during the execution of weight lifting exercises. The electrogoniometer consists of four microelectromechanical accelerometers connected to a microcontroller. The microcontroller is connected via USB to a computer. Preliminary tests show that the system offers high precision and accuracy at angle measurement. Error in the measured values is less than 0.3% when comparing to a commercial digital goniometer, and it is low cost. © 2014 IEEE.